Design and Characterization of Polymeric Nanoparticles of Pioglitazone Hydrochloride and Study the Effect of Formulation Variables Using QbD Approach - Canchi, Adhokshaja; Khosa, Archana; Singhvi, Gautam; Banerjee, Saswata; Dubey, Sunil K. (Current Nanomaterials, 2017)
Background and Objective: Pioglitazone hydrochloride is a BCS Cass II drug used for hypoglycemic action which shows poor bioavailability post oral administration due to poor solubility in gastrointestinal fluids. The purpose of this study was to prepare and characterize the polymeric nanoparticles of pioglitazone using polycaprolactone (PCL) as polymer and study the effect of various formulation parameters on the nanoparticle characteristics. Method: Drug loaded polymeric nanoparticles were fabricated by nanoprecipitation method, using PCL and Poloxamer 188 as a surfactant. Results: The nanoparticles produced were assessed for particle size (187.4 to 249.5 nm), zeta potential (-20 to -33), PDI (0.138 to 0.347), percentage entrapment efficiency (62.23 to 76.39), drug content (2.09 to 3.56) and in-vitro drug release study (controlled up to 12h). Various process and formulation parameters such as rate and time of stirring, polymer content, surfactant concentration, drug loading were optimized using 32 factorial design (QbD) approach. Conclusion: Results indicated that polymer-surfactant ratio plays an important role in the design of nanoparticles.
Keywords: polymeric nanoparticles